Degradation resistance of different cementitious materials to phosphoric acid attack at early stage. (January 2022) - Ren, Jie; Zhang, Lihai; Walkley, Brant; Black, Jay R.; San Nicolas, Rackel
Abstract: Sewer wastewater systems pose great threats to OPC-based concretes used for pipes due to the presence of various acids. Phosphoric acid can cause as much damage as sulphuric acid but has been very lightly studied. This study focuses on the early stage of the degradation process of different cementitious materials in phosphoric acid. Three types of cementitious materials are compared: OPC (100% cement), slag-blended OPC (slag/cement mass ratio at 65/35) and alkali-activated slag/fly ash pastes (slag/fly ash mass ratio at 50/50). Samples were exposed to phosphoric acid solution with a constant pH at 2.0 ± 0.2 for 44 days. The degradation kinetics, chemical and microstructural properties as well as dissolution rate of these binders are analysed. The results show that the alkali-activated slag/fly ash binder has the lowest degradation rate compared to the other cement-based binders. The intrinsic characteristics of the binders lead to significant changes in the kinetics of degradation. The chemical properties of the binders are the critical influential factor of the early stage behaviour. A conceptual degradation process is proposed to describe the early-stage kinetics of degradation for the cementitious materials studied. Graphical abstract: Schematic diagram showing the early stage degradation processes of AASF and OPC-based pastes exposed to the phosphoric acid. ADD-Apparent degradation depth; DD-Dissolved/detached depth. Unlabelled Image